👤

3
Ştiind că:
1. a = ( 6 +3:3-5): 2
b = 5-4: (8-6:1)
c=(7 +9):4-3x(8-2x4)
b=
C=
a =​


Răspuns :

Răspuns:

1.) a = ( 6 +3:3-5): 2

a= (6+1-5):2

a=2 (oops)

2.)b = 5-4: (8-6:1)

b= 5-4:(8-6)

b=5-4:2

b=5-2

b=3

3.)c=(7 +9):4-3x(8-2x4)

c=16:4 -3×(8-8)

c=4-3×0

c=4-0

c=4

[tex]a = (6 + 1 - 5) \div 2 \\ a = (7 - 5) \div 2 \\ a = 2 \div 2 \\ a = 2[/tex]

[tex]b = 5 - 4 \div (8 - 6 \div 1) \\ b = 5 - 4 \div (8 - 6) \\ b = 5 - 4 \div 2 \\ b = 5 - 2 \\ b = 3[/tex]

[tex]c = (7 + 9) \div 4 - 3 \times (8 - 2 \times 4) \\ c = 16 \div 4 - 3 \times (8 - 8) \\ c = 4 - 3 \times 0 \\ c = 4 - 0 \\ c = 4[/tex]